2020
DOI: 10.1177/1747021820938659
|View full text |Cite
|
Sign up to set email alerts
|

Comparing unfamiliar voice and face identity perception using identity sorting tasks

Abstract: Identity sorting tasks, in which participants sort multiple naturally varying stimuli of usually two identities into perceived identities, have recently gained popularity in voice and face processing research. In both modalities, participants who are unfamiliar with the identities tend to perceive multiple stimuli of the same identity as different people and thus fail to “tell people together.” These similarities across modalities suggest that modality-general mechanisms may underpin sorting behaviour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Johnson, McGettigan and Lavan's (2020) results suggest that these similarities in findings across modalities may indeed be underpinned by some common processes, as performance in face and voice sorting tasks was correlated, albeit weakly. Consistent with faces providing more reliable identity cues, Johnson et al (2020) also found that face sorting was more accurate than voice sorting using a "free" identity sorting task, in which participants are unaware of the veridical number of identities and thus decisions can be highly inaccurate (see also Jenkins et al, 2011;Lavan, Burston, & Garrido, 2019). However, face advantages are also seen for "forced" sorting, where participants are instructed about how many identities are represented by the stimuli: in these tasks, accuracy is higher for both faces and voices compared to free sorting, but where forced facesorting tends to be near-perfect (Andrews, Jenkins, Cursiter, & Burton, 2015), voice sorting remains relatively error-prone .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Johnson, McGettigan and Lavan's (2020) results suggest that these similarities in findings across modalities may indeed be underpinned by some common processes, as performance in face and voice sorting tasks was correlated, albeit weakly. Consistent with faces providing more reliable identity cues, Johnson et al (2020) also found that face sorting was more accurate than voice sorting using a "free" identity sorting task, in which participants are unaware of the veridical number of identities and thus decisions can be highly inaccurate (see also Jenkins et al, 2011;Lavan, Burston, & Garrido, 2019). However, face advantages are also seen for "forced" sorting, where participants are instructed about how many identities are represented by the stimuli: in these tasks, accuracy is higher for both faces and voices compared to free sorting, but where forced facesorting tends to be near-perfect (Andrews, Jenkins, Cursiter, & Burton, 2015), voice sorting remains relatively error-prone .…”
Section: Introductionmentioning
confidence: 79%
“…In identity sorting tasks, where participants are instructed to sort a set of naturally varying stimuli into different identities, it is common to incorrectly perceive multiple images or recordings of the same unfamiliar person as representing a number of different people (Jenkins, White, Van Montfort, & Burton, 2011;Lavan, Burston, & Garrido, 2019;Stevenage, Symons, Fletcher, & Coen, 2020). Johnson, McGettigan and Lavan's (2020) results suggest that these similarities in findings across modalities may indeed be underpinned by some common processes, as performance in face and voice sorting tasks was correlated, albeit weakly. Consistent with faces providing more reliable identity cues, Johnson et al (2020) also found that face sorting was more accurate than voice sorting using a "free" identity sorting task, in which participants are unaware of the veridical number of identities and thus decisions can be highly inaccurate (see also Jenkins et al, 2011;Lavan, Burston, & Garrido, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…We suggest more data are required to better individual differences in card-sorting tasks and their influence, if any, on related facial identity tasks (cf. Johnson et al., 2020; Stacchi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The other articles in this virtual special issue were published subsequently and have adopted some or all of these suggestions. Broadly, these articles fall into three categories, comprising research that has directly examined the benefit of studying face identification with multiple images ( Andrews et al, 2015 , 2017 ; Dowsett et al, 2016 ; Jones et al, 2017 ; Longmore et al, 2017 ; Menon et al, 2015 ; Ritchie & Burton, 2017 ); research with designs that incorporate multiple images of faces across all conditions ( Bortolon et al, 2018 ; Hayward et al, 2017 ; Tuettenberg & Wiese, 2019 ); and recent work on voice recognition that is adapting these research methods from the face domain ( Johnson et al, 2020 ; Lavan et al, 2019 ; Stevenage et al, 2020 ).…”
mentioning
confidence: 99%
“… Bortolon et al (2018) employed several ambient images per identity to study self-recognition under more natural viewing conditions than in previous studies. And the sorting tasks that have been developed to research within-person variability in face matching have now also been adapted to study vocal identity ( Lavan et al, 2019 ; Stevenage et al, 2020 ) and to compare face and voice perception ( Johnson et al, 2020 ). This demonstrates that the study of within-person variability continues to grow in interest and scope.…”
mentioning
confidence: 99%